Robust stability and performance analysis of a longitudinal aircraft model using sum of squares techniques - Papachristodoulou, A; Papageorgiou, C; IEEE (2005)
In this paper we demonstrate how the recently developed sum of squares techniques can be used to analyze robust stability and robust performance of quasi-LPV models. We show the effectiveness of the methodology through the analysis of the stability and performance of a nonlinear control law applied to an uncertain quasi-LPV model of the short-period dynamics of an F/A-18 aircraft. ©2005 IEEE.